Filogeografia de Trichomycterus (siluriformes: Trichomycteridae) na Mata Atlântica - Volpi, Thaís de Assis (2017)
Trichomycterinae is a subfamily of catfishes that comprises of eight genera, which are monotypic or composed of few species, and the only exception is Trichomycterus, represented by 161 nominal species distributed in the neotropical region. The genus is polyphyletic due to several taxonomic problems involving the species, which makes difficult the understanding of the distribution patterns of its lineages, since the difficulty in delimiting them. Thus, the present study aimed to recover the hierarchical relationships of Trichomycterus to verify the distribution pattern of the lineages. For this, the study was conducted in three stages: (i) Reconstruct the phylogenetic lineages of the neotropical Trichomycterus using 456 sequences of the cit-b with 999 bp distributed from the Chilean Andes to the west, Guyana to the north and all of eastern Brazil ; (ii) To propose the hierarchy and delimitation of the Trichomycterus lineages genus in a phylogenetic perspective, using 496 sequences of the COI with 789 bp distributed from Rio de Contas at the north to Jacuí at the south , area covering the type-locality of the species-type of the genus, T. nigricans; (iii) Verify the distribution of the 496 animals and the phylogeographic patterns of the species. We found three geographically structured clades (west X north X eastern), divergent between 12.5 and 15% were recovered, the eastern clade being more distinct from the others. The western clade, composed of T. areolatus, species of other genera of Trichomycterinae were recovered. Whereas T. nigricans are found in eastern Brazil, we suggest that Trichomycterus be represented by species from the east, and that T. areolatus and Bullockia be rellocated to Hatcheria. In the eastern portion, we delimit 18 species through DNA Barcoding protocol. Also we observed two clades geographically structured with divergence of 11.8%, suggesting the existence of two genera in the eastern. Such hierarchy would minimize the current problems of the genus, making it monophyletic. From the analysis of species distribution patterns, it was verified that 55% of them are found in the headwaters of the São Francisco, Paraná and Paraíba do Sul. This region had great importance in the evolutionary history of the group, as ancestral area, dispersal routes, and species refuges, given the shared history of most of them associated with the portion. In addition, we verified that the endemism of species which are restricted to a single basin occurred in only 28% of cases, refuting the premise of endemism for most species of the genus. Population geographic structuring was verified at basin level. In the cases in which do not pattern of distribution of the lineages was verified, it was possible to infer that the population structure would be related to the past conformation of the landscape. We found that even within phylogenetically related lineages and sister-species, the phylogeographic patterns are very distinct, varying according to the amplitude of their distribution and the environment in which they are found.